Reply: Biogenic structures of unioniform bivalves in wet-interdune deposits (late miocene-warly pliocene, Argentina) - Carmona, Noelia Beatriz (2019)
Fil: Carmona, Noelia B. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología; Argentina.